Examining racial and gender biases in teaching evaluations of instructors by students on an online platform in the UAE - Lamba, Nishtha; Kishore, Sameer; Khokhlova, Olga (Frontiers in Education, 2023)
This research investigates whether biases based on instructors' gender (male, female) and race (White and South Asian) influence university students' perception of instructors in an online teaching environment in the UAE. Using a between group design, 318 participants viewed one of the four videos (male-South Asian, female-South Asian, male-White, female-White) of a virtual instructor teaching social psychology. Biases showcased consistent preference for male and South Asian lecturers. However, biases emerged in interpersonal variables, such as approachability, sensitivity, enthusiasm for subject, and respect, and not in the domains of knowledge, presentation skills, and stimulating thinking. Findings further reinforce that relying on teaching evaluations may not be accurate, and highlight how certain unconscious biases could impact professional growth of academics.